Analysis of complete mitochondrial genome sequence of Kessleri thrush, Turdus kessleri (Passeriformes, Turdidae). Issue 2 (3rd July 2018) - Song, Sen; Qin, Jiahui; Luo, Juanjuan; Li, Donghai; Jiang, Bo; Chang, Cheng
Abstract: In this study, the complete mitochondrial genome of T. kessleri was sequenced and characterized. The overall base composition of T. kessleri mitogenome is 29.3% for A, 32.3% for C, 15.0% for G, and 23.5% for T. The percentage of G + C content is 47.2%. The mitogenome is a circular DNA molecule of 16, 754 bp in length, including a D-loop region, two rRNA genes (12SrRNA and 16SrRNA), 13 protein-coding genes (PCGs), and 22 tRNA genes. The sequence information of T. kessleri can contribute to enrich the molecular data resources about birds and could also enable the phylogenetic research and help to resolve phylogenetic relationship problems related to Turdus .